Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Pada Café Ngunjuk Indonesia di Kabupaten Tangerang - Farchan Ramadhan Dian Syakuron; Putri Nilam Kencana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of product quality and promotion on purchasing decisions at Café Ngunjuk Indonesia in Tangerang Regency both partially and simultaneously. The method used is quantitative. The sample in this study amounted to 99 respondents. Data analysis uses simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis (r2), partial test (t test), and simultaneous test (f test). The results of this study are a discussion of the effect of service quality (X1) and promotion (X2) on customer satisfaction (Y), as follows: The product quality variable (X1) has a very significant influence on purchasing decisions (Y), it can be seen based on the results of the correlation coefficient test, which is 0.945, meaning that the two variables have a very strong level of relationship. Based on the value of the coefficient of determination or contribution of its influence is 89.4% while the rest (100% -89.4%) = 10.6% is influenced by other factors. The promotion variable (X2) has a significant influence on purchasing decisions (Y), as evidenced by the correlation coefficient test, which is 0.951, indicating a very strong relationship between the two variables. The coefficient of determination, or contribution, accounts for 90.4% of the influence, while the remaining 9.6% (100%-90.4%) is influenced by other factors. The product quality (X1) and promotion (X2) variables significantly influence purchasing decisions (Y), as evidenced by the correlation coefficient test, or the level of relationship between the independent and dependent variables, of 0.929, indicating a very strong relationship. The coefficient of determination, or contribution, simultaneously accounts for 93.2% of the influence, while the remaining 6.8% (100%-93.2%) is influenced by other factors.